Beam test results of high-density glass scintillator tiles - Du Dejing; Hua Zhehao; Liu Yong; Qi Baohua; Sen Qian (EPJ Web of Conferences)
To achieve the physics goal of precisely measuring the Higgs, Z, W bosons and the top quark, future electron-positron colliders, such as the Circular Electron Positron Collider (CEPC), require that their detector systems have unprecedented high jet energy resolution. Based on the particle flow algorithm (PFA), a new high-granularity hadronic calorimeter with glass scintillator tiles (GSHCAL) has been proposed, focusing on the significant improvement of hadronic energy resolution with a notable increase of the energy sampling fraction by using high-density glass scintillator tiles. The Glass Scintillator R&D Collaboration group is dedicated to developing high-performance glass scintillators to meet the requirements of high-energy physics experiments. The minimum ionizing particle (MIP) response of a glass scintillator tile is crucial to the hadronic calorimeter, so a dedicated test system was developed for testing the performance of glass scintillator tiles. Two beam tests on large glass scintillator tiles at CERN and DESY have been carried out, and the MIP response of glass scintillator tiles was demonstrated to reach 100 p.e./MIP, which essentially meets the design requirements of the GSHCAL. This contribution will introduce the dedicated test system and also present highlighted beam test results.